Variable time Quantum Based Round Robin Policy for Cloud Computing Environment - Zaidi, T; Shukla, S (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing provides on demand accessibility of resources with transparency.The cloud composed of serveral datacenters and customers may acess the computational resources over a network provisioned by cloud service provider. The challenge in cloud environment is to meeting customers demand succesfully by allocating of computational resources.Scheduling is an important criteria that effects performance of systems.Round robin is a preemptive scheduling policy that effects the performance of systems as it provides fairness in scheduling tasks in cloud environment.The current work is based on the time varying time quatum strategy that deals with maximum cpu utilization and minimizes the waiting time,Tunraronud time,Average turn around time ,context switching and provides better performance.